Observation of ground surface roughness values obtained by stylus profilometer and white light interferometer for common metal materials. (18th January 2022) - Lu, Enhui; Zhang, Ruting; Liu, Jian; Yin, Shaohui; Ohmori, Hitoshi
Abstract : To find some practical understandings and to derive some rules for roughness calibration for common metal materials, this paper counts surface roughness on 50 ground workpieces of five different materials obtained by a stylus profilometer (here‐in‐after, 'SP') and a white light interferometer (here‐in‐after, 'WLI'). The materials include iron, stainless steel, 45 steel, copper and aluminium on which hardness values are widely ranged. The results show that SP measurement result is generally smaller than WLI measurement result for its stylus tip size and scratches on surface. The SP method has obvious scratches on soft materials (Al and Cu), which leads to the reduction of low spatial frequency information on the measured profile. WLI measurement result is more accurate when measured surface is smooth while SP is more suitable for rough and hard surface roughness measurement.